Tapioca Starch Coagulant for Landfill Leachate Treatment - Nur Shaylinda Mohd Zin; Siti Nor Aishah Mohd Salleh; Hamidi Abdul Aziz (2024)
Coagulation-flocculation is applied for various wastewater such as sewage, industrial, and leachate, which has the proven ability to remove pollutants through a solid-liquid separation process. Coagulant is a material added during coagulation with chemical coagulants used conventionally. However, using natural coagulants to replace chemical coagulants is widely studied. This book highlights the application of natural tapioca starch coagulant for the coagulation-flocculation of stabilised leachate. This book’s content is also regarded as an alternative solution for leachate treatment for landfill management. This book first presented information on landfills and leachate, followed by starch as a natural coagulant from a previous study. It compiles the research study and highlights the application of natural coagulants made from starch tapioca flour and tapioca peel in the form of single, dual and composite coagulants. Finally, it helps academics, researchers, and students better understand the application of natural starch-root coagulant for treating landfill leachate.